The Expectation of 3rd year Chinese Majored Students Faculty of Humanities and Social Sciences Rajabhat Mahasarakham University for Teaching and Learning Processes of Southwest Forestry University - ทองกระจาย, อัญชนา; Qi, Qin (Chophayom Journal, 2019)
The purpose of the current study was to study six aspects of expectation including quality of Chinese instructors, curriculum and learning resources, teacher roles, student roles, learning media, and evaluation and assessment of 3rd year Chinese majored students for teaching and learning processes of Southwest Forestry University using genders and GPA as dependent variables. The samples were 79, 3rd year Chinese majored students in 2018 academic year selected by the purposive sampling method. Independent variables are basic information of students consisting of gender and grade point average. The following variables are expectations of students in the 3rd year of Chinese Majors. The instrument was a questionnaire designed in five Likert scales. The statistics used in data analysis were Percentage, Mean Score, Standard Deviation, and t-test (Independent Samples), and F-test (one-way ANOVA). The results of the study were as follows. 1. The expectation for teaching and learning processes of Southwest Forestry University of 3rd year Chinese majored students was found at a high level. All aspects of expectation were found at a high level. In detail, the aspects of curriculum and learning resources, evaluation and assessment, teacher roles, quality of Chinese instructors, learning media, and student roles were found to be a descending order of expectation. 2. There were significant differences between the expectations of the students for teaching and learning processes of Southwest Forestry with different genders in terms of curriculum and learning resources, learning media, and evaluation at the statistical level of .05 while there was no significant difference in other aspects. 3. There were significant differences between the expectations of the students with different GPAs for teaching and learning processes of Southwest Forestry in terms of Chinese instructors at the statistical level of .05 while there was no significant difference in other aspects. The research results show that 3rd year Chinese Majored Students have expectations about the teaching and learning process in every area. Therefore, the course can use this research result as a database for the development of efficient Chinese teaching and learning. There are guidelines for promoting Chinese language teaching in schools that offer Chinese language. For quality and for all parties with vested interests resulting in satisfaction. Keywords : Chinese Majored, Chinese teaching and learning process, Thai Chinese learners